Clinical summary of intravenous use of vancomycin hydrochloride for severe indection caused by methicillin-resistant Staphylococcus aureus - Shimada Kaoru; Kobayashi Hiroyoshi; Sunakawa Keisuke; Inamatsu Takashi; Yamaguchi Keizou (Japanese Journal of Chemotherapy, 1995)
Vancomycin hydrochloride (VCM) for injection has been marketed since November 1991 as an indication severe for infections caused by methicillin-resistant Staphylococcus aureus (MRSA). The overall results of post-marketing surveillance for the past three years are shown below.The subjects were 1, 354 patients to whem the drug was intravenously administered in a study period from December 1991 to October 1994 in 650 facilities, and a total of 1, 255 cases were chosen among them as the subjects for evaluation of efficacy excluding 99 cases which the physicians in charge had classified as unable to judge. Daily doses of the drug were 40 mg/kg for children, and 1 g or 2 g for adults for a period of 1-3 weeks. In addition, decrease in daily dose as well as shortening of the administration period were observed with time. When observed improvement rates according to diseases, the improvement rate was 78. 7% for pneumonia, and 87.5% for sepsis, exhibiting an improvement rate of 81.7% as a whole. On the other hand, the improvement rates were higher for the patients who had not been given a previous drug, but, no difference was observed in the improvement rates among daily doses or in patients with or without concomitant drugs. The antibacterial effect was 64.2% for pneumonia, and 88.5% for sepsis, 69.8% bacterial eradication rate as a whole. There were 271 episodes of subjective or objective adverse reactions and abnormal laboratory findings in 191 patients (14.1%). Especially for the abnormal laboratory findings on renal function, the incidence in the adult and elderly patients was higher for the patients daily dose of 2 g than that for those with 1 g daily. The plasma level monitoring was performed in 1, 082 cases in 500 patients out of 1, 354 patients (36.9%)(2.2 cases per 1 patient). The rates of monitoring practice were showing an increasing trend in accordance with progress of year. Pharmacokinetics analysis revealed decrease in creatinine clearance (Ccr) in many cases of the elderly patients. A linear relationship was observed among elimination constant (e), VCM clearance, and Ccr. A β-phase elimination half-life (t1/2 β) was extended, accompanying with decrease in Ccr, and even for the cases withmild decrease in renalfunction the elimination half-life was prolonged to nearly three times the value of healthy adults. The above results thus obtained prove that the VCM injection is a highly useful drug showing the sufficient effects for MRSA infection and is thereby considered best to immediately administer to the cases in which phlogogenous bacteria is identified as MRSA. Adverse reaction can be minimized when in use, if appropriate use and dose are applied by performing the plasma level monitoring along with consideration of ages and renal function. 注射用塩酸バンコマイシン (VCM) はメチシリン耐性黄色ブドウ球菌 (MRSA) による重症感染症を適応症として1991年11月に発売された。その後3年聞の市販後調査の集計成績は次のとおりである。対象は全国650施設で1991年12月から1994年10月に本剤を静脈内投与された1,354例で, 安全性は全例を, 有効性は判定不能99例を除く1,255例を評価対象例とした。本剤の1日投与iは小児では40mg/kg, 成人では19または29で, 1～3週間投与が多かった。また, 経年的に1日投与iの減少傾向, 投与期間の短縮傾向がみられた。疾患別改善率は, 肺炎78.7%, 敗血症87.5%などで全体で8L7%であった。また, 先行薬なしの症例で改善率が高かったが, 1日投与量, 併用薬の有無による改善率の差はみられなかった。MRSAに対する細菌学的効果は, 肺炎64.2%, 敗血症88.5%などで全体で69-8%の菌消失率が得られた。自他覚的副作用および臨床検査値異常は191例 (14.1%) のべ271件発現した。特に腎機能検査値異常については, 成人, 高齢者ともに発現頻度は1日2g投与が1日19投与より2倍以上高かった。血中濃度モニタリングは1,354例中500例 (36.9%), 1,082件 (1例当たり2.2件) 実施された。実施率は経年`的に増加していた。薬動学的解析対象は高齢者のクレアチニンクリアランス (Ccr) 低下例が多かった。消失速度定数 (Ke), VCMクリアランスとCcrには直線関係がみられた。β相半減期 (t1/2β) はCcrの低下に伴い延長し, 腎機能軽度低下例でも健常人の3倍近く延長していた。以上の成績より、注射用VCMはMRSA感染症に対し適確な効果を示す有用性の高い薬剤であり, 起炎菌がMRSAと確認された症例に対しては速やかに投与すべきであると思われる。使用の際には年齢と腎機能を考慮し, 血中濃度モニタリングを実施して適正な用法・用量を選択すれば副作用も抑制できると考えられる。